NILAI MANFAAT BIMBINGAN DAN KONSELING BELAJAR TERHADAP SISWA: STUDI KEPUSTAKAAN - Mulia, Riza (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: Generally, students have a negative mindset towards the existence of learning guidance and counseling at school. This research was conducted to examine the usefulness of learning guidance and counseling for students at school. Considering that students are apathetic towards learning guidance and counseling services when they experience problems with learning at school. As a result, the implementation of learning guidance and counseling programs is considered less effective. The research procedure used was qualitative, the researcher chose a literature review approach by searching and reviewing literature in the form of scientific journal articles and books with the same theme. The results of the literature review in this research state the function of learning guidance and counseling, namely overcoming student learning problems, preparing students' futures, and increasing students' personal maturity. It is necessary to disseminate information about the value of the benefits of learning guidance and counseling to students and the entire school.Keywords: benefit, guidance; counseling; student.Abstrak: Umumnya siswa memiliki maindset negatif terhadap keberadaan bimbingan dan konseling belajar di sekolah. Penelitian ini dilakukan untuk mengkaji nilai kebergunaan bimbingan dan konseling belajar untuk siswa di sekolah. Mengingat siswa bersikap apatis terhadap layanan bimbingan dan konseling belajar ketika mengalami masalah dengan pembelajaran di sekolah. Akibatnya, pelaksanaaan program bimbingan dan konseling belajar dianggap kurang efektif. Prosedur penelitian yang digunakan adalah kualitatif, peneliti memilih pendekatan kajian kepustakaan dengan menelusuri dan mengkaji literatur berupa artikel jurnal ilmiah maupun buku yang setema. Hasil kajian pustaka dalam penelitin ini menyatakan fungsi bimbingan dan konseling belajar, yaitu mengatasai problem belajar siswa, menyiapkan masa depan siswa, serta meningkatkan kematangan diri siswa. Perlu dilakukan sosialisasi tentang nilai manfaat bimbingan dan konseling belajar kepada siswa, dan seluruh pihak sekolah. Kata Kunci: manfaat; bimbingan; konseling; siswa.